Charcoal sampling and gas chromatographic determination of N,N-dimethylformamide in air samples from a polyurethane plant. - Rimatori, Valentino; Carelli, Giovanni (Scandinavian Journal of Work, Environment & Health, 1982)
A charcoal sampling method and a gas chromatographic determination of N,N-dimethylformamide in the air of a plant producing polyurethane lumps is described. The collection efficiency was checked by drawing standard N,N-dimethylformamide air mixtures through the sampling tube at 0.1 1/min and detecting the organic vapors spectrophotometrically at 215.4 nm. At 1,000 mg/m3, samplings could be carried out for 190 min with negligible N,N-dimethylformamide losses (lower than 1%). The analysis of N,N-dimethylformamide was performed by gas chromatography on Porapack Q and Tenax GC after extraction with 2 ml of acetone/100 mg of charcoal, with a mean recovery of 90 (SD 2)%, in the range of 0.05-0.5 mg of N,N-dimethylformamide/100 mg of charcoal. The relative standard deviation of the entire procedure was 3.5%. Because of the good adsorbing efficiency of the charcoal, short-term sampling could be carried out at a relatively high N,N-dimethylformamide concentration. Stationary and personal sampling resulted in mean values ranging between 1.26 and 1.60 mg/m3. The method is particularly suitable in instances where other pollutants are present, and therefore it can be used also for other work areas as well.
Keywords: air pollution; air sample; charcoal; charcoal sampling; frontal analysis; gas chromatography; industrial hygiene; N,N-dimethylformamide; polyurethane plant; sampling